A thermally tunable THz metamaterial frequency-selective surface based on barium strontium titanate thin film. (15th November 2018) - Dong, Bowen; Ma, Hua; Wang, Jun; Shi, Peng; Li, Jiang; Zhu, Liguo; Lou, Jing; Feng, Mingde; Qu, Shaobo
Abstract: In this paper we propose a design method for a thermally tunable frequency-selective surface (FSS) in the THz frequency range employing barium strontium titanate (BST) thin film. Due to the excellent thermoelectric properties of BST, different relative permittivities can be obtained at different temperatures. With this ability, the passband frequency of the FSS can be tuned by changing the temperature of the BST thin film. The metallic element array of the FSS is designed using the metamaterial method. A convenient method for thermal control is proposed that uses micro-fabricated electric heating wires; these can provide different temperatures by altering the input electric current. Full wave simulations show good performance of thermally tunable frequency selective transmission at THz frequencies. The proposed FSS is then fabricated and measured. The experimental results agree well with the simulation. By changing the temperature of the BST thin film, the passband can be tuned from 0.826 THz to 0.905 THz. This work proposes a THz tunable FSS based on BST thin film, which promotes connections between ferroelectric films and tunable THz functional devices.